Modeling of Solitary Wave Interaction with Curved Face Seawalls Using Numerical Method - Seyyed-Mahmood Ghassemizadeh; Mohammad Javad Ketabdari (Advances in Civil Engineering)
This paper considers the solitary wave interaction with seawalls of different curved geometries and sloped faces using numerical modeling. This interaction was simulated using the Finite Volume Method-Volume of Fraction (FVM-VOF) approach. To model the turbulent free-surface flow, coupled VOF and k-ε-RNG methods were used. To validate the model, the numerical results for a conventional sloping seawall were compared with the available experimental data. Then the interaction of solitary waves and seawalls with different sinusoidal, logarithmic, and parabolic functions front faces and linear slope was modeled. The results showed that for these seawalls in general by increasing the solitary wavelength, the wave reflection coefficient (Cr) increases. However, the wave run-up on seawalls demonstrates an oscillatory decrease. Furthermore, for parabolic walls in comparison to conventional linear sloping seawalls, the wave run-up and wave reflection increased by 4.1% and 4.7%. For sinusoidal walls, the wave run-up and wave reflection increased by 5% and 1.8%. For logarithmic walls, the wave run-up and wave reflection increased by 6.3% and decreased by 1.1%, respectively. This means that wave run-up on logarithmic walls is more than that of the sinusoidal, parabolic, and sloped walls. The simulation results revealed that normalized maximum run-up increases with an increase in normalized incident wave height for all types of curved walls.